Coding What do You want to findout ? Fun facts, Amazing pictures, Quizzes - Kelly, James Floyd; Davey, Lizzie; Hobson, Emma (London Dorling Kindersley Limited, 2017)
Have you ever wanted to know how computers think? Or what a computerbug is? Packed with fascinating facts and pictures form the world of coding, this is a small book filled with big ideas
The world around us (Computer)
1 2
Keywords: Coding theory -- Juvenile literature; Computer programming -- Juvenile literature